Implementing Wordwall Assisted by TaRL Approach to Improve English Vocabulary Mastery - Herlinda, Nika; Tjalla , Magdahalena; Sunubi, Abdul Haris; Fakhruddin, Zulfah; Mujahidah, Mujahidah (IAIN KENDARI, 2026)
English vocabulary mastery is one of the fundamental aspects of language learning that supports students’ ability to understand and use English effectively. However, many elementary school students still experience difficulties in understanding, remembering, spelling, and using English vocabulary. This study aimed to improve the English vocabulary mastery of fourth-grade students through the implementation of Wordwall assisted by TaRL approach and to investigate students’ responses toward its use in English vocabulary learning. The study employeed Classroom Action Research followed Kemmis and McTaggart’s model and involved 22 fourth-grade students across two cycles. Instruments included vocabulary tests and observation sheets. Quantitative data came from students’ test scores, while qualitative data were obtained from observations and field notes during the actions. Combining TaRL to map student abilities with Wordwall as a gamified medium distinguishes this study from prior research. Findings indicate the intervention effectively increased students’ vocabulary mastery. The average score rose from 53.14 in the initial test to 84.09 in Cycle II. The percentage meeting the minimum completeness criteria (KKM) increased from 36.36% initially to 90.91% in Cycle II. Observations also revealed positive student responses, shown by increased participation, involvement, enthusiasm, and self-confidence during learning. In conclusion, integrating Wordwall with the TaRL approach is an effective strategy for improving elementary students’ English vocabulary. The approach offers a practical, student-centered way for teachers to enhance vocabulary mastery and make learning more engaging.